(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3bGd Ydi Hf GdYHGS (B: (3Ef CMb CeG HYO (B: (3abO CSYO Gddg Gdedc GdLdjd , GdcQje GdYfUQ , GdaGVd GdLhgQ s
(3BNQgG (B:s
(3ef GdLRA GdKGfi ef cJGH cGed GdUfGYI GdWHjI hgj GdebGdI GdYTQhf ef CUd GdcJGH Ydi Hf GdYHGS GdeJWHH hced GdcJGH HCeQg haQZ ef fSNI s
(3UfYI dYVO GdOhdI Hf Hhjgs
(3hQJHg Yi YTQjf ebGdIs
(3ai cd LRA YTQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs